Pro Deo et Pro Patria : the contribution of Blessed Edmund Ignatius Rice and his Christian Brothers to the philosophy and structures of nineteenth century Irish education - Kelly, Donal (Don) A. (Trinity College (Dublin, Ireland). School of Education, 2000)
The aim of this thesis is to provide a balanced and factual evaluation of the subject matter outlined in the title of the work. The two opening chapters provide an historical account of educational provision for Catholics in the 18th century in Ireland in general. These chapters also take account of the efforts of Catholic individuals, both lay and clerical, to circumvent the Penal Laws against Catholic education in various locations, initially on an ad hoc basis and later in a more structured fonn.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin